The "Double Standard" of Nonproliferation: Regime Type and the U.S. Response to Nuclear Weapons Program - Alina Shymanska (International Journal of Nuclear Security, 2018)
There is no doubt that the NPT regime is far from being equal for all states involved. As the predominant hegemonic power since WWII, the United States plays a major role in deciding the fates of non-great power proliferators. This article tries to find the logical explanation of the phenomenon whereby some nuclear proliferators are absolved regardless of their active accumulation of nuclear arsenals while others are labeled as “rogue states” and ordered to disarm. The article suggests that a particular proliferator’s political regime could affect the way in which its state is approached by the U.S., known for its loyalty to democratic values. To check this argument’s feasibility, the author analyzes and compares types of political regimes of proliferators—which refer to non-great powers that commenced their nuclear programs since 1964. The study also shows that alignment with the U.S. and presence or absence of hostility toward the West are also influential factors. Along with the proliferator’s political regime, these factors determine whether the country is necessarily absolved, required to disarm, or heavily punished. The author finds that the U.S. tends to free democratic proliferators from charges, especially those aligned with the U.S., officially or unofficially. In most cases, the autocratic governments are coerced to give up their proliferation ambitions, though an alignment with the U.S. may work as an extenuating circumstance to render the punishment less harmful. The article aims to demonstrate that the U.S.’s tendency to coerce undemocratic de facto nuclear powers, while avoiding coercion against democratic partners, is not a mere “double standard” or bias, but rather, a part of the U.S.’s strategic policy.
Keywords: nuclear nonproliferation; the United States; non-great powers; democracy; autocracy; anocracy; democratization; coercive diplomacy; engagement